ANALISIS FREKUENSI MAKAN DAN PENDAPATAN KELUARGA TERHADAP KEJADIAN STUNTING PADA BALITA USIA 12–59 BULAN DI DESA LEBAK PARAHIANG WILAYAH KERJA PUSKESMAS LEUWIDAMAR TAHUN 2025 - Ivan Panji Teguh; Roslina; Rita Ariesta; Dwi Apriyanti; Adelia Ikka Rahilla (Jurnal Obstretika Scientia, 2025)
Stunting, defined as a height-age below -2 standard deviations of WHO standards, remains a major public health problem affecting children from the prenatal period up to two years of age. This study aimed to examine the association between nutritional intake and socioeconomic status with stunting among children aged 12-59 months in Lebak Parahiang Village, 2025. An observational analytic study with a case-control design was conducted invloving 67 respondents in the working area of ​​Leuwidamar public health center. Data on nutritional intake, socioeconomic characteristics, and child growth indicators were collected and analyzed. Most respondents were housewives (88.2%) with an average monthly household income of approximately IDR 2,000,000. Growth assessment revealed that 41% of children were undernourished. Based on weight-for-age, 43.8% had normal nutritional status, where as about one-third showed mild to severe undernutrition. Based on weight-for-height, 76% were in good condition, indicating adequate nutritional intake in most children. Findings emphasized the significant role of maternal involvement and economic support in preventing stunting. Strengthening maternal education, improving access to promote optimal feeding practices, and ensuring regular growth monitoring. References: 19 (2020-2025)